The Influence of Leadership Style and Interpersonal Communication on Employee Performance with Work Morale as an Intervening Variable at PT. Surya Andalan Primatama Mukomuko - Neneng Supatri; Ramdani Bayu Putra; Mutia Seplinda; Hasmaynelis Fitri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of leadership style and interpersonal communication on employee performance with work enthusiasm as an intervening variable at PT. Surya Andalan Primatama Mukomuko. The population and research sample were 110 respondents with a sampling technique using the total sampling method. The data processing method uses Structure equation modeling (SEM) with the SmartPLS tool. The research results show that there is a significant positive influence of leadership style and interpersonal communication on work morale. Leadership style has a positive and significant effect on employee performance, and interpersonal communication has a positive and insignificant effect on employee performance. Work morale has a positive and significant influence on employee performance. For indirect effects, this research also reveals that leadership style and interpersonal communication influence employee performance through work morale